Protecting pollinators and our food supply: understanding and managing threats to pollinator health - Siviter, H.; Fisher, A.; Baer, B.; Brown, M. J.F.; Camargo, I. F. [UNESP]; Cole, J.; Le Conte, Y.; Dorin, B.; Evans, J. D.; Farina, W.; Fine, J.; Fischer, L. R.; et al. (Springer Nature, 2023)
Global pollinator declines threaten food production and natural ecosystems. The drivers of declines are complicated and driven by numerous factors such as pesticide use, loss of habitat, rising pathogens due to commercial bee keeping and climate change. Halting and reversing pollinator declines will require a multidisciplinary approach and international cooperation. Here, we summarize 20 presentations given in the symposium ‘Protecting pollinators and our food supply: Understanding and managing threats to pollinator health’ at the 19th Congress of the International Union for the Study of Social Insects in San Diego, 2022. We then synthesize the key findings and discuss future research areas such as better understanding the impact of anthropogenic stressors on wild bees.